PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS PADA RUMAH MAKAN WAJAN MAS KUDUS) - Denny Aditya Rachman; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2017)
The development and competition of the culinary services business is increasing rapidly. They compete in providing the best service to retain their customers. This research was conducted on Rumah Makan (RM) Wajan Mas Kudus. From sales data of RM Wajan Mas Kudus it can be found that there are fluctuations of sales and amount of RM Wajan Mas Kudus consumer’s complaints related service quality and food delicacy. As a company that engaged in service sector, RM Wajan Mas Kudus must provide good service to its customers, good service is equal with price according to what is given by RM Wajan Mas Kudus.This study aims to determine the effect of service quality (X1) and price (X2) on consumer purchasing decisions (Y) on RM Wajan Mas Kudus. Type of research that used is explanatory research with data collection methods using interviews and data collection tools using questionnaires with a sample of 100 respondents RM Wajan Mas Kudus customers using the Purposive Sampling method. The analysis technique used are validity test, reliability test, simple linear regression, multiple linear regression, t test, and F test with SPSS 16.From the result of research indicate that service quality have strong influence to purchasing decision equal to 61,4%, while price influence strong enough to decision of purchase equal to 34,3%. It shows that service quality variable to purchase decision variable has higher influence than price variable.Researcher suggests to improve purchase decision is to improve the service quality of RM Wajan Mas Kudus which is considered important by the service user but still get less attention from the company, such as the willingness of employees in serving the needs of the consumers, provide a clear menu list, the willingness of employees in serving each complaint, friendliness and courtesy of employees to consumers, as well as recognizing consumers as customers.